MODEL EXPERIMENTS WITH 31 M TRAWL AND COMPARISON WITH FIELD TRIALS - Perumal, M C; Mukundan, M; Rajendran, R (Indian Journal of Fisheries, 2011)
A model of a 31 m two-seam trawl was tested in a towing tank. The horizontaland vertical openings and warp tension were measured at various speeds. Observationsat speeds varying from 0.24 to 0.41Sm/sec indicated that the tension and horizontalspread increase with increasing speed, whereas the vertical opening showed a decrease.At the designed speed of 0.37S m/sec, lOS.S cm and ll.S cm were the horizontal andvertical openings respectivdy and the tension was 61S gm. The values were predictedfor the full-scale net and were compared with the field observations. In the case ofh